2000
DOI: 10.1590/s0102-09352000000100017
|View full text |Cite
|
Sign up to set email alerts
|

Potencial reprodutivo e econômico de touros Nelore acasalados coletivamente na proporção de um touro para 80 vacas

Abstract: Utilizaram-se 15 touros selecionados entre 158, por meio de exame andrológico, qualidades físicas e morfológicas do sêmen e biometria testicular (teste 1) e de comportamento sexual (teste 2) que os classificaram de bons a excelentes. Organizaram-se dois grupos experimentais, G1 e G2, o primeiro composto por cinco touros e 400 vacas, estabelecendo, assim, a proporção de um touro para 80 vacas e o segundo, considerado como testemunha, de 10 touros e 400 vacas, portanto, proporção de 1:40. Todas as matrizes eram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
8

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 4 publications
0
3
0
8
Order By: Relevance
“…In Brazil, a higher percentage of abnormal sperm after high temperature and relative humidity observed a higher ejaculate volume in the rainy season [11]. Studying the Nellore cattle concluded that semen characteristics may be affected by environment, by high ambient temperature, air humidity and photoperiod [12]. Studies on the environmental influence on semen quality in bulls have been conducted in farmers with bulls in permanent regime of semen collection [8].…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, a higher percentage of abnormal sperm after high temperature and relative humidity observed a higher ejaculate volume in the rainy season [11]. Studying the Nellore cattle concluded that semen characteristics may be affected by environment, by high ambient temperature, air humidity and photoperiod [12]. Studies on the environmental influence on semen quality in bulls have been conducted in farmers with bulls in permanent regime of semen collection [8].…”
Section: Introductionmentioning
confidence: 99%
“…Tradicionalmente, os pecuaristas adotam a proporção touro:vaca de 1:25 que, segundo Fonseca et al (1996) e Fonseca et al (2000), resulta em subutilização dos touros e, conseqüentemente, torna a monta natural uma prática antieconômica.…”
unclassified
“…Diversos estudos têm sido realizados no Brasil visando aumentar a proporção touro:vaca para 1:40, 1:60, 1:80, 1:92 ou mesmo 1:96, com o objetivo de maximizar o potencial reprodutivo dos touros, a fim de aumentar a eficiência reprodutiva do rebanho e reduzir os custos (Fonseca et al, 1991;Pineda e Lemos, 1994;Pineda et al, 1997a,b;Galvani, 1998;Fonseca et al, 2000), contudo, os dados obtidos ainda não são conclusivos.…”
unclassified
See 1 more Smart Citation
“…BSE is an economically feasible technology which, combined with other changes in management practices, may improve revenues of breeders. Sereno et al (2002), Fonseca (2000) and Franco et al (2006) found a benefit/cost ratio of US$ 8.24, US$ 12.32 and US$ 13.83, respectively. These values were obtained from the change in the rate of herd bulls based on the use of bulls whose reproductive efficiency could be ascertained.…”
Section: Resultsmentioning
confidence: 99%